2018
DOI: 10.1038/s41477-018-0151-8
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation diversity protects against childhood asthma: results from a large New Zealand birth cohort

Abstract: We assessed the association between the natural environment and asthma in 49,956 New Zealand children born in 1998 and followed up until 2016 using routinely collected data. Children who lived in greener areas, as measured by the normalized difference vegetation index, were less likely to be asthmatic: a 1 s.d. increase in normalized difference vegetation index was associated with a 6.0% (95% CI 1.9-9.9%) lower risk of asthma. Vegetation diversity was also protective: a 1 s.d. increase in the number of natural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 46 publications
1
92
0
1
Order By: Relevance
“…A decreased risk of asthma was also reported in association with an increase in NDVI value at individual level [30]. Moreover, children living in more vegetated areas in New Zeeland showed a lower risk of having asthma [39]. Other authors reported no association between greenness and asthma.…”
Section: Discussionmentioning
confidence: 83%
“…A decreased risk of asthma was also reported in association with an increase in NDVI value at individual level [30]. Moreover, children living in more vegetated areas in New Zeeland showed a lower risk of having asthma [39]. Other authors reported no association between greenness and asthma.…”
Section: Discussionmentioning
confidence: 83%
“…Similarly, exposure to the natural environment is associated with increased social connectivity,37 and social isolation can increase individual reactivity to opioids38 as well as being a risk factor for premature mortality 39. More recently, research suggests that exposure to the natural environment may increase the microbial diversity of the human microbiome,40 and protect against adverse health outcomes41 through improved immune function. In addition, improved immune function is associated with improved surgical recovery42 and better orthopaedic outcomes in elderly patients 43…”
Section: Discussionmentioning
confidence: 99%
“…Based on the meta-analysis of Barton and Pretty [ 32 ], every green environment improved self-esteem and mood, but spending time near a waterside (e.g., beach or river) or participating in water-based activities generated greater effects. An increased diversity of ecosystems has also been associated with a decreased risk of asthma in children [ 61 ] and an increased number of rare yard plants with a decreased risk of allergic sensitization in teenagers [ 62 ].…”
Section: Characteristics Of Second Homes and Potential Health Benementioning
confidence: 99%